PERFORMANCE MONITORING OF MICROSERVICE-BASED SYSTEMS (Uzbekistan Open Conference, 2025)
Within the framework of this study, a microservice application was developed using two different approaches: traditional and reactive programming using the Spring framework. Load tests have been conducted to assess which approach best meets the requirements of high-load systems.